SDR's, currencies, and gold : seventh survey of new legal developments - Gold, Joseph (Washington, D.C. : International Monetary Fund : Copies from External Relations Dept., Attention Publications, International Monetary Fund, 1987)
This book provides list of currencies that determine the value of the SDR and the amounts of these currencies, shall be revised with effect on January 1, 1986 which will be revised every five years.
Bibliography: p. 129-145.
usc 21/09/18
Loans
Keywords: Money--Law and legislation; Special drawing rights; Gold--Law and legislation; Foreign exchange